The relation among tertiary education, technical designs and patents - Daan van Dongen; Gloria Gheno (Discover Education)
Abstract This study examines the relationships between education metrics, gender equity, and innovation outcomes in the context of technological advancements and globalization, focusing on Asian nations. Using the Gross Enrollment Ratio (GER) for tertiary education and the Adjusted Gender Parity Index (GPIA), the research investigates each country's commitment to higher education and gender inclusion. The findings highlight that increased GER, when supported by robust research expenditure, positively influences innovation outcomes such as patent numbers and technical design advancements. However, GPIA introduces a complex dynamic, negatively affecting these outcomes despite higher educational enrollment and research investment. The study underscores the importance of interdisciplinary collaboration, hands-on curricula, and public–private partnerships in enhancing practical education relevance and mitigating gender disparities. Ultimately, it advocates for a balanced, inclusive approach to education and research to foster sustainable technological innovation.